UPAYA MENINGKATKAN MOTIVASI DAN HASIL BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENTS DILENGKAPI CROSSWORD PUZZLE SISWA KELAS VIIIC SMP NEGERI 3 SAWANGAN MAGELANG - Erma Dwi Anggraeni; A. A Sujadi; sri adi widodo (Universitas Sarjanawiyata Tamansiswa, 2014)
The purpose of this research is to improve students' motivation and learning outcomes in mathematics through cooperative learning type Teams Games Tournaments (TGT) completed with crossword puzzle method in class VIII C SMP Negeri 3 Sawangan Magelang. This research is Classroom Action Research (CAR) conducted in two cycles. The subjects of this research is students of class VIII C SMP Negeri 3 Magelang Sawangan totaling 30 students. Data collection techniques in this research uses observation, questionnaires, tests and documentation. The results showed that motivation and mathematics learning outcomes has increased. Based on the results of research, math teachers can implement Teams Games Tournaments (TGT) which is completed with crossword puzzle method as a variation in mathematics learning model.